PLEA FOR FAIR PLAY - JURAVLE Mariana (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The personal essence of victory in the Olympic arena allowed the athletes in major international confrontations to demonstrate originality in an amazing physical and psychological potential. Victory and defeat are inseparable: "win or lose", both are part of sport and life. The power to impose our extensive oxygenation morality, campaigns to show the young generation, who are true heroes, that are models worthy to follow. The example is the only certain virtue.